The Experience of Insomnia in Patients With Schizophrenic Disorder: A Qualitative Study - Batalla-Martín, David; Martorell-Poveda, Maria-Antonia; Belzunegui-Eraso, Angel; Miralles Garijo, Eva; Del-Cuerpo Serratosa, Ana; Valdearcos Pérez, JuanCarlos; Montané Escobar, Miquel; Lopez-Ruiz, Marina (Frontiers in Psychiatry, 2022)
Abstract Background: Insomnia is a health problem that particularly affects people with schizophrenia. Its repercussions go beyond the disorder itself and affect many areas of life. The aim of the present study is to explore the clinical symptoms and consequences of insomnia in patients diagnosed with schizophrenic disorder and the perceptions of these patients regarding the care they receive. Methods: The study takes a qualitative approach and uses semi-structured interviews to conduct a descriptive and interpretive analysis of 3 clinically different clusters of patients. These 3 clusters have been defined by using two-step cluster analysis based on the results of the ISI (Insomnia Severity Index) and EQ-5D scales (EuroQol-5D) and the presence of certain diagnostic symptoms in a sample of 170 patients. The final sample was 31 subjects. The analysis was based on a hermeneutic analysis of the patients’ narratives regarding their experiences of insomnia. Results: The patients’ narratives show differences in the intensity and experience of insomnia depending on the severity, as well as its impact on their quality of life. Insomnia has a huge emotional impact. Participants describe ruminations and obsessive thoughts as a key factor hindering falling asleep. Some of the everyday actions they perform encourage the chronicity of insomnia. The desired health response must include interventions that are effective, such as cognitive-behavioural therapy, and powerful, such as pharmacological solutions. Psychoeducation and advice on sleep hygiene are highly valued tools as preventive strategies. Conclusions: To know the experience of users gives us a more comprehensive understanding of insomnia complexities and brings some new intervention strategies in patients with mental disorders. It is important that health professionals intervene preventively to stop the disorder from becoming chronic.